TRANSLATION OF SOMATIC PHRASEOLOGICAL UNITS IN GERMAN AND UZBEK - Nurullayev Khasan Tukhtayevich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article outlines the problems and features of the translation of somatic phraseological units in German and Uzbek, and also describes the important factors that must be taken into account, as well as the problematic framework for the translation of phraseology. The theoretical opinions of linguists are analyzed. When translating phrases, they have a very complex meaning structure, and as a result, it is difficult to find an alternative in the second language with a completely semantic structure. The article briefly analyzes these problems.